Predictors of Adverse Alcohol Use Consequences Among Tertiary Students. (13th March 2019) - Poulton, Antoinette; Mata, Adrienn; Pan, Jason; Bruns, Loren Richard; Sinnott, Richard O.; Hester, Robert
Abstract : Background: The alcohol consumption patterns of young adults are of concern. Critically, tertiary students consume greater quantities of alcohol, are at increased risk of injury/harm, and have higher rates of alcohol use disorders as compared to their nonuniversity enrolled peers. The Brief Young Adult Alcohol Consequences Questionnaire (BYAACQ) is one of several tools utilized to explore adverse alcohol‐related outcomes among tertiary students. Alcohol intake behavior, assessed via retrospective summary measures, has been linked to BYAACQ score. It is unclear, however, how drinking assessed in real time, in conjunction with variables such as age of drinking onset, might predict severity of adverse alcohol consequences as captured by the BYAACQ. Methods: The psychometric properties of the BYAACQ were explored using a large Australian sample of tertiary students ( N = 893). A subsample ( n = 504) provided alcohol intake information in real time (21 days; event and notification contingent) via a smartphone app (CNLab‐A) plus details related to age of drinking onset, drug use, parental alcohol/drug use, and anxiety/depression symptomology. Results: Average BYAACQ score was 7.53 (SD = 5.37). Classical and item response theory analyses revealed inconsistencies related to dimensionality, progressive item severity, and male/female differential item functioning. Current drinking—namely, frequency of intake and quantity per drinking occasion—plus age of drinking onset predicted BYAACQ score after controlling for age, other drug use, and depression symptomology. Conclusions: The BYAACQ is a sound tool for use with Australian samples. Information related to current drinking, age of drinking onset, and drug use is useful for predicting severity of alcohol use consequences. These markers might enable tertiary institutions to better target students who could benefit from prevention/intervention programs. Abstract : Among tertiary students, alcohol intake behaviour, assessed using retrospective summary measures, has been linked to adverse alcohol‐related outcomes, as indexed by the Brief Young Adult Alcohol Consequences Questionnaire (BYAACQ). It is unclear, however, how drinking assessed in real‐time might predict severity of adverse alcohol consequences. We found current drinking—measured via an app in real‐time—plus age of drinking onset predicted BYAACQ score after controlling for age, other drug use, and depression symptomology.